Multichannel Staggered SAR Azimuth Sample Regularization - De Almeida, Felipe Queiroz; Krieger, Gerhard (European Conference on Synthetic Aperture Radar (EUSAR), 2016)
Next-generation spaceborne SAR systems pose demanding and contradicting requirements on system design, owing to the increasing need to cover ultra-wide swaths with high azimuth resolution, as required for numerous applications. To this end, a large number of multichannel SAR system concepts have been proposed that employ digital beamforming on receive with planar arrays, and more recently also with reflector antennas. A promising concept is staggered SAR which uses a single azimuth channel and multiple elevation beams together with variable pulse repetition intervals to map an arbitrary wide swath with medium resolution. To improve the azimuth resolution, this paper extends the staggered SAR concept to a system configuration with multiple azimuth channels. For this, a new multichannel azimuth processing technique is introduced that combines staggered SAR gap interpolation with multi-channel SAR signal reconstruction. Simulations of a Tandem-L-like reflector SAR system with three azimuth channels show that this technique yields an excellent performance over a 350 km wide swath that is mapped with 3.0 m azimuth resolution.
DLR Import::2019-04-03